KEEFEKTIFAN METODE PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA KULIAH CHOUKAI III (Penelitian Eksperimen Terhadap Mahasiswa Bahasa Jepang Tingkat II Tahun Ajaran 2016/2017 FKIP Universitas Riau) - Syahwil Nasution; Nana Rahayu; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This study discusses about the Effectiveness of Cooperative Learning Method Type Jigsaw On Material Choukai III For Javanese Deparment Student FKIP UR. The purpose of this study is to know how the result of learning student in class before and after using in cooperative learning method type Jigsaw material of Choukai III, and how the student interaction in class before and after using in learning cooperative method type Jigsaw in Choukai material. The object of this study is the Javanese Deparment Student FKIP UR at grade II. In this study the writer used research design weak eksperimen is designed with pretest before doing the test and posttest after doing the test. Data accumulation technique have been done by giving the test and observing. The result test in this pretest and posttest used statistic test t- by using manual test for knowing some big level of result significance student learning when used learning Jigsaw type. Based on statistic data processing t-by manual test is got = 8 and = 2.1 (standart significance 5%) > so is unaccepted and accepted. It’s means that there is significance contrast to ward effectiveness of coorperatif learning method type Jigsaw on material Choukai III at student grade II in academic 2016/2017 Javanese FKIP Riau University.Key Words: Kooperatif Learning Method Type Jigsaw, Choukai III, Weak Eksperimen